2019
DOI: 10.1038/s41390-019-0563-9
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan 35 kDa enhances epithelial barrier function and protects against the development of murine necrotizing enterocolitis

Abstract: Background-Disruption of tight junctions (TJ) predisposes to bacterial translocation, intestinal inflammation, and necrotizing enterocolitis (NEC). Previously studies showed that hyaluronan (HA), a glycosaminoglycan in human milk, maintains intestinal permeability, enhances intestinal immunity, and reduces intestinal infections. In this study, we investigated the effects of HA 35 kDa, on a NEC-like murine model. Methods-Pups were divided into Sham, NEC, NEC + HA 35, and HA 35. Severity of intestinal injury was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 39 publications
(65 reference statements)
3
33
0
Order By: Relevance
“…Hill et al [173] demonstrated a polydisperse HM HA extract is capable of protecting colonocytes from Salmonella infection in vitro. Mice treated with HA 35 are protected from Citrobacter rodentium infection via an upregulation in the critical tight junction protein, ZO-1 (zonula occludens-1), resulting in reduced intestinal permeability and inhibited bacterial translocation across colonic epithelium [193], similar to our findings in a murine NEC model [179].…”
Section: Glycosaminoglycan Protection Against Necsupporting
confidence: 86%
See 1 more Smart Citation
“…Hill et al [173] demonstrated a polydisperse HM HA extract is capable of protecting colonocytes from Salmonella infection in vitro. Mice treated with HA 35 are protected from Citrobacter rodentium infection via an upregulation in the critical tight junction protein, ZO-1 (zonula occludens-1), resulting in reduced intestinal permeability and inhibited bacterial translocation across colonic epithelium [193], similar to our findings in a murine NEC model [179].…”
Section: Glycosaminoglycan Protection Against Necsupporting
confidence: 86%
“…Our group recently demonstrated the effectiveness of HA 35 in reducing the incidence and severity of disease in a mouse model of necrotizing enterocolitis. Gunasekaran et al [179] treated mouse pups (age P14-16) with HA 35 (15 mg/kg or 30 mg/kg) once per day for three days prior to the initiation of NEC. NEC was induced using a two-hit model of intraperitoneal dithizone injection followed by oral administration of Klebsiella pneumoniae [55].…”
Section: Glycosaminoglycan Protection Against Necmentioning
confidence: 99%
“…With these abundant issues associated with NEC, it is incumbent upon researchers to develop targeted, specific treatments for the disease. BM components, such as human milk saccharides (i.e., oligosaccharides like 2'-fucosyllactose and glycosaminoglycans like hyaluronan) and anti-microbial peptides (i.e., lactoferrin), have proven to have some efficacy in the treatment of NEC [93,112,113].…”
Section: Breast Milk Extracellular Vesicles and Necrotizing Enterocolmentioning
confidence: 99%
“…The first one occurs at the local cellular level. HA binds to specific cell surface receptors such as CD44, (9,10) Undefined Topical Treatment for interstitial cystitis/painful bladder syndrome (11) HA 750 kDa IP Proliferation of colonic epithelium in vivo (12) HA 750 kDa IP Protection from DSS-induced colitis in vitro and in vivo (13) HA 750 kDa IP Protection from irradiation in vivo (14) HA (20) HA molecular mass and route of administration appear to be important for specific efficacy.…”
Section: Hyaluronanmentioning
confidence: 99%